Strategi Humas Museum Kehutanan Manggala Wanabakti Jakarta Dalam Meningkatkan Minat Pengunjung Museum - Utomo, Ichsan (Jurnal Public Relations (J-PR), 2020)
This research is a research on how to use SWOT analysis in advancing an organization. The formulation of the problem in this research is "How is the Public Relations Strategy of the Manggala Wanabakti Jakarta Forestry Museum in Increasing Visitors' Interest". The method used is SWOT analysis and uses descriptive qualitative research methods. By providing a matrix for discussion, it was found that the organization can first analyze the internal organization and can find a description of the problem in increasing visitor interest.